The Correlation Between Working Conditions And Nurse Work Stress At Pratama Gerbang Sehat Mahulu Hospital Mahakam Ulu District - Petronius Ding; Ratanto Ratanto; Amiruddin Amiruddin (MNJ (Mahakam Nursing Journal), 2023)
Abstract Working conditions in the hospital are activity, the physical condition of the room, or the nurse's activity at work regarding the comfort of the nurse in working. Work stress on nurses is one of the problems such as decreased enthusiasm for work and work performance if this is left unchecked it will have an impact on increasing the risk of errors occurring in interventions that will endanger the patient or the nurse itself. The puspose of this this research to find out the correlation between working conditions and the work stress of nurses at Pratama Gerbang Sehat Mahulu Hospital Mahakam Ulu District. The research design used by researcher in this study was an analytic study with a cross-sectional approach with a total sample of 53 people. Bivariate analysis used a non-parametric statistical test, namely Chi-square using a significant level of α < 0.05. Obtained a p-value of 0.026 (<0.05) which means that H1 is accepted and H0 is rejected, meaning that there is a significant correlation between working conditions and work stress of nurses at Pratama Gerbang Sehat Mahulu Hospital Mahakam Ulu District in 2023. Keywords: Working Conditions, Nurse Work Stress